Profil Dan Kesulitan Pemecahan Masalah Matematika Berdasarkan Taksonomi SOLO - Sunardi Sunardi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This research examined both the students’ understanding of mathematical problems and their difficulties in solving the problems based on the SOLO taxonomy. The Collis-Romberg test of mathematical problem solving consisting of five items, each having four questions, was administered to 582 first-year students from 15 classes of public senior high schools in Jember. The results indicated that 8.82%, 7.73%, 33.30%, 34.67%, and 16.01% of the students were respectively at prestructural, unistructural, multistructural, relational, and extended abstract levels. The students’ difficulties were identified as follows: they did not understand the stems; they did not understand the questions; and they did not understand the concepts of digit and number, double proportion, and locus of points.